Utilization of paravertebral nerve blocks as part of a multimodal analgesic regimen in a patient with Bernard-Soulier syndrome undergoing a Nuss procedure - Bojaxhi, Elird (Rom J Anaesth Intensive Care, 2016)
We present a case of regional analgesia utilized in a 43-year-old woman with Bernard-Soulier syndrome (BSS) undergoing a Nuss procedure for the treatment of pectus excavatum. BSS is an extremely rare bleeding disorder (1:1,000,000) associated with prolonged bleeding times, giant platelets, and thrombocytopenia. Due to the rare incidence and heterogeneity in bleeding predisposition due to BSS, there is no clear consensus in management of such cases, and to our knowledge, utilization of regional analgesic techniques have not been described in the literature. The Nuss procedure is considered “minimally” invasive, and epidural analgesia is frequently utilized at our institution. Due to our patient’s heterozygous presentation of BSS and mild history of bleeding, a modified perioperative multimodal analgesic plan was chosen which included bilateral single injection paravertebral nerve blocks (PVBs). Our report describes successful utilization of PVBs in a patient with BSS and our approach to this rare hereditary condition.